PERAN KOMUNIKASI EFEKTIF PEMIMPIN DALAM MENINGKATKAN KINERJA INSTITUSI - Binti Nasukah; Sulistyorini Sulistyorini; Endah Winarti (JURNAL AL-TANZIM, 2020)
This study aims to identify and understand two important things, namely; characteristics of effective communication of school principals and the role of effective communication of school principals in improving institutional performance. This research uses a qualitative approach to the type of library research, by collecting data from; books, kitab, journals, articles. Data analysis was performed using content analysis. Through the literature study, the results show that: first, there are six characteristics of effective communication of leaders: being gentle, not being rude in speech, not being stubborn, forgiving and asking for forgiveness, inviting deliberation, and committed to conducting joint decisions and resignation to Allah SWT. Second, effective communication leaders play a role in; 1) Increase the effectiveness in sharing the vision of the Mission; 2) Improving the performance of the staff in the teacher's specialty; 3) Establishing partnerships with the school community 4) building a conducive school climate; and 5) Increasing the students' achievements. The results implicates on the importance of leaders of Islamic institutions to have the characteristics of effective communication, so it can play a role in improving the performance of the Institution.